Stress catcher application for mobile stress monitoring using questionnaire-based - Aslina Baharum; Siti Hasnah Tanalol; Cheng Xu Jian; Muhammad Omar; Noorsidi Aizuddin Mat Noor; Nurhafizah Moziyana Mohd Yusop (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Nowadays, stress has become the main reason to cause health problems. The human’s lifestyle has been increasing due to the fast development of technologies which help to improve performance and productivity indirectly increased the burden of human lifestyle. Many studies have done to identify the cause of stress and the effect of stress among university students. However, stress monitoring is not well mentioned in the previous works especially stress monitoring with questionnaire-based. Thus, this research tried to come out with a mobile application that fit to use to monitor the stress level by using a questionnaire. Mobile-D used to identify and develop the mobile application, namely as Stress Catcher. Mobile-D approach allows Test-driven development and it is suitable to use for mobile applications development. A prototype of Stress Catcher will function to prove the usefulness in human lifestyle.